Extensibility of the myofilaments in vertebrate skeletal muscle as revealed by stretching rigor muscle fibers (The Rockefeller University Press, 1983)
The extensibility of the myofilaments in vertebrate skeletal muscle was studied by stretching glycerinated rabbit psoas muscle fibers in rigor state and examining the resulting extension of sarcomere structures under an electron microscope. Although stretches applied to rigor fibers produced a successive yielding of the weakest sarcomeres, the length of the remaining intact sarcomeres in many myofibrils was fairly uniform, being definitely longer than the sarcomeres in the control, nonstretched part of rigor fibers. The stretch-induced increase in sarcomere length was found to be taken up by the extension of the H zone and the I band, whereas the amount of overlap between the thick and thin filaments did not change appreciably with stretches of 10-20%. The thick filament extension in the H zone was localized in the bare regions, whereas the thin filament extension in the I band appeared to take place uniformly along the filament length. No marked increase in the Z-line width was observed even with stretches of 20-30%. These results clearly demonstrate the extensibility of the thick and thin filaments. The possible contribution of the myofilament compliance to the series elastic component (SEC) in vertebrate skeletal muscle fibers is discussed on the basis of the electron microscopic data and the force-extension curve of the SEC in rigor fibers.